Integral use of umari (Poraqueiba sericea Tulasne) for the preparation of flours and incorporation into gluten-free pan bread mix (Research, Society and Development, 2022)
The objective of this work was the full use of umari (Poraqueiba sericea Tulasne) for the elaboration of flours and incorporation in gluten-free pan bread mix, verifying the impact on quality parameters and bioactive compounds. For this, physicochemical and quality parameters (proteins, lipids, carbohydrates, energy value, beta carotene, fatty acids, minerals) were analyzed. The shelf life of the product was also measured over 180 days (pH, color, moisture, acidity, AW, peroxide index and mold, yeast and insect infestation counts). The mixtures enriched with lyophilized umari pulp and residue showed higher lipid contents (10.89g and 9.07g respectively) and higher energy values ​​(399.83kcal and 386.01kcal, respectively). The enriched mixtures presented ideal values ​​of pH, color, humidity, acidity, AW, peroxide index, mold count, yeast and insect infestation over 180 days. The addition of lyophilized pulp, lyophilized umari residue, umari pulp flour and umari residue flour led to an increase in oleic acid in relation to the control bread. We could also observe an increase in magnesium in the mixtures enriched with the various umari powders and flours and a decrease in sodium levels. The supplementation of umari powders and flours in the gluten-free bread mix was a useful and efficient approach to obtain a quality product with good physicochemical parameters in storage for six months.